Ethnobotanical observations on tribe Arnatans of Nilambur Forest, Western Ghats region of Kerala, India - Thomas, Binu; Mathews, Ranji P.; Rajendran, A.; Prabhu Kumar, K.M. (Research in Plant Biology, 2013)
The ethnobotanical observation on tribe Arnatans of Nilambur region reveals that, They utilize numerous plants and their various parts viz., leaves, bark, roots and rhizome etc. for both internal and external applications were involved in the treatment of various ailments in their daily life. A total of 30- species of medicinal plants belonging to 28- families have been collected.